2016
DOI: 10.1089/cap.2015.0241
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar Disorder Type 1 in a 17-Year-Old Girl with Wolfram Syndrome

Abstract: Given the complexity of WS, this case suggests that the possible association between WS and BD should not only be merely limited to a possible statistical association with WFS1 polymorphism but also to developmental, cognitive, and endocrine risk factors for BD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Wolfram syndrome patients may develop psychiatric disorders (56), such as bipolar disorder, schizophrenia, anxiety, and depression (57)(58)(59). Surprisingly, changes in NCS1 abundance provoke similar symptoms in human and mice (60,61).…”
Section: Discussionmentioning
confidence: 99%
“…Wolfram syndrome patients may develop psychiatric disorders (56), such as bipolar disorder, schizophrenia, anxiety, and depression (57)(58)(59). Surprisingly, changes in NCS1 abundance provoke similar symptoms in human and mice (60,61).…”
Section: Discussionmentioning
confidence: 99%
“…Deafness and DI are present in 46 and 29% of the patients, respectively ( 4 ). Other symptoms could include urinary disorders, pons atrophy, ataxia ( 4 , 5 ), and psychiatric disorders, including bipolar disorder ( 6 ), schizophrenia ( 7 ), suicide ( 8 ), or mania ( 9 ). To date, no treatment is available, and most of the affected patients die prematurely.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, p.Ala684Val had a higher in silico impact based on Combined Annotation Dependent Depletion (CADD) ( https://cadd.gs.washington.edu/ ) and Rare Exome Variant Ensemble Learner (REVEL) ( https://sites.google.com/site/revelgenomics/ ) algorithms, with scores of 28.8 and 0.891, respectively. Functional research has established the pathogenicity of the p.Ala684Val variant [ 19 ] and alternative variant (p.Ala684Thr) with corresponding residues [ 39 , 40 ]. Co-segregation analysis confirmed that the two variants segregated as de novo trait in three unrelated families (Fig.…”
Section: Resultsmentioning
confidence: 99%